Physiology and secondary metabolite production in genetically trasformed brahmi(Bacopa monnieri L wettst) with cytokinin synthesizing isopentenyl transferase (ipt) gene. - Vighnesha (Department of Plant Physiology, College of Agriculture, 2007)
An experiment was conducted in the Department of Plant Physiology, College of Agriculture, Vellayani, to overexpress cytokinin synthesizing ipt gene in Bacopa monnieri through Agrobacterium tumefaciens mediated transformation and to regenerate the transformed plants through tissue culture for analyzing the influence of overexpression of ipt gene on growth, physiology and secondary metabolite production. The transformation and molecular works were done in Rajiv Gandhi Center for Biotechnology, Trivandrum. Escherichia coli strain JM 109 was transformed independently with pBI B33 ipt and pBI SAG12 ipt. Triparental mating was done using Agrobacterium tumefaciens strain EHA 105, pRK 2013 and recombinant E.coli. Plasmids were isolated from recombinant E.coli and recombinant Agrobacterium cells to confirm the successful transformation of constructs. Both have showed the insertion release when double digested with restriction enzymes EcoRI and HindIII. Pre incubated leaf explants of Bacopa monnieri were co-cultivated with the recombinant Agrobacterium for two days and transferred to regeneration medium containing MS supplemented with 2mgl-1 BA, 15mgl-1 kanamycin and 300mgl-1 cefotaxime. Putative transformants were regenerated from co-cultivated explants when placed on the selection medium containing 15mg/l kanamycin and 300mg/l cefotaxime. Uninfected explants failed to regenerate in presence of kanamycin. Rooting was not found in the MS medium devoid of growth regulators. Sub culturing of shootlets was done in MS medium supplemented with 1ppm GA and 1ppm IAA. Hardening was done to the fully rooted plants and were kept in five replications for further analysis. DNA was isolated from both wild type and transformants. PCR amplification for nptII and ipt gene specific primers showed presence of gene in transformants but not in the wild type. From the selected transformants, RNA was isolated and RT-PCR was done. RT-PCR analysis confirmed the expression of ipt and nptII gene in all the transformants, while there was no expression in the wild type. Expression of constitutively expressed plant gene –actin was used as loading control. Southern hybridization of PCR amplified products gave the evidence for the presence of ipt gene only in transformants but not in wild type. Physiological and biometric observations were performed on both transformants and wild type which served as control over the transformants. Plant height was more in transformants compared to the wild. Both root length and relative water content was more in wild compared to the transformants. Other parameters like number of branches and number of leaves were higher in the transformants than in the wild. Total chlorophyll, chlorophyll a and chlorophyll b were found to increase for first five weeks in all treatments, after that there was a decrease in the total chlorophyll, chlorophyll a and b in wild type but transformants were able to retain higher contents throughout the period of study. Total soluble protein content was higher in the transformants than the wild type. Stomatal frequency showed a significant difference between the treatments. Higher number of stomata was observed in the transgenics compared to the wild type. The distribution of stomata also differed significantly. In wild type the distribution was equal in both upper and lower surface of leaf but in transformants a higher number of stomata were observed at the lower surface than the upper surface. Cytokinin content was estimated using ELISA. There was a significant variation in cytokinin, iPA concentration between wild type and transformants. Transformants had higher cytokinin content than the wild type. The transformant with B33 promoter had more cytokinin content than transformant with SAG promoter. Bacoside, the major secondary metabolite of the plant was estimated by HPLC and its content between the wild type and transformants were found to be on par. In this experiment, the overexpression of ipt gene in bacopa resulted a higher amount of cytokinin in transgenics and hence had higher growth rate, protein and pigment content. Overexpression of ipt may not increase the bacoside content in the bacopa.